1985
DOI: 10.1212/wnl.35.9.1357
|View full text |Cite
|
Sign up to set email alerts
|

Familial Paroxysmal hypnogenic dystonia

Abstract: We studied a family with dystonic spasms that occurred with non-REM sleep. This familial disorder may be related to the sporadic cases reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The first reports of paroxysmal hypnogenic dyskinesia came from Horner and Jackson in 1969 describing two families with "familial paroxysmal choreoathetosis" [14]. Other familial and non-familial cases have since been reported [22,26,33,38]. Close inspection of these hypnogenic cases reveals that they are not at all similar to typical PKC.…”
Section: Discussionmentioning
confidence: 99%
“…The first reports of paroxysmal hypnogenic dyskinesia came from Horner and Jackson in 1969 describing two families with "familial paroxysmal choreoathetosis" [14]. Other familial and non-familial cases have since been reported [22,26,33,38]. Close inspection of these hypnogenic cases reveals that they are not at all similar to typical PKC.…”
Section: Discussionmentioning
confidence: 99%
“…Lugaresi and Cirignotta (45) introduced the term nocturnal PD when describing a group of patients with frequent brief, sleep‐related attacks characterized by predominantly dystonic movements. Lack of any ictal or interictal scalp EEG abnormality has added to the difficulty in correctly diagnosing the nature of such episodes, as confirmed by several subsequent reports (9,46–48). Although it took 20 years from the first description by Lugaresi and Cirignotta (45) before the paroxysmal dystonia‐like nocturnal episodes were found to be accompanied by ictal scalp EEG activity in a few patients (49), previous studies with depth electrodes had demonstrated that similar attacks were actually the expression of seizure activity in the mesial frontal lobe (46,50).…”
Section: Paroxysmal Dyskinesia Versus Epilepsymentioning
confidence: 95%
“…CAP is indeed a natural arousal rhythm reflecting unstable vigilance, a favorable condition for triggering different types of motor activity, from physiological body movements (16) to nocturnal myoclonus (19), parasomnias (3,18,40) and epileptic manifestations (21,25,(41)(42)(43)(44)(45)(46)(47). Arranged in recurring windows of permission (phase (18) 258 (35) 59 ( 9) 88 (29) 20 ( 6) 95 (39) 21 ( 7) 204 (43) 406 (5 1) 27 ( 5) 11 ( 3) 16 ( 4) 52 ( 4 Tables 1 and 2.…”
Section: Iu-mentioning
confidence: 99%